Relations between entrepreneur’s social identity and strategic entrepreneurship: Sustainable leadership as mediator - Liu, Gang; Yin, Qing; Zhang, Leyi (Frontiers in Psychology, 2022)
Although there are studies verifying that strategic entrepreneurship is positively related to the risk resistance and performance of enterprises, it is unclear how enterprises can implement effective strategic entrepreneurial activities in dynamic situations. This research aims to explore why and how the entrepreneur's social identity influences and drives firm’s strategic entrepreneurial activities. In this study, it applied case study method to interview a technology-based family firms that have effectively conducted strategic entrepreneurial activities to meet challenges, and uses grounded theory for data analysis. The research finds that (1) the social identity of entrepreneurs actively promotes the strategic entrepreneurial activities of enterprises; (2) sustainable leadership mediates the relationship between social identity and strategic entrepreneurship; (3) at different stages of enterprise development, entrepreneurs dynamically adjust their social identity types to enhance sustainable leadership; (4)through the focus and extension of technological advantages, sustainable leadership ensures that enterprises can promote the implementation of strategic entrepreneurial behavior by disintegrating and integrating the value chain. This study explores the strategic entrepreneurship path of family firms, and also provides new insights for future research on the strategic entrepreneurship and sustainable growth of such firms.